Young people and parent or carers views on type 2 diabetes mellitus care in England and Wales: analysis of parent and patient-reported measures survey - Pooja Sachdev; Katherine Hawton; Hannah Hickingbotham (BMJ Paediatrics Open)
Background The prevalence of type 2 diabetes mellitus (T2DM) in children and young people (CYP) is increasing in the UK and worldwide. Little is known about the experience young people and their families have when attending for their diabetes care. The aim of this study is to analyse the responses to the Parent and Patient Reported Experience Measures (PREM) survey 2021–2022 for patients with T2DM and their families to inform care.Methods As part of the National Paediatric Diabetes Audit (NPDA) (2022), the NPDA PREM survey was open online between August 2021 and January 2022. The data have previously been analysed collectively for all diabetes; however, we specifically analysed the data for patients living with T2DM.Results 9.2% (105/1144) of young people living with T2DM in England and Wales responded to the NPDA PREM survey, mostly aged 12–16 years (61.9%) and the majority were female (67.6%). 87% of patients and 95% of carers said that they would recommend their diabetes team, and 73% of patients felt happy after appointments. Only just over half of the patients and parents felt well prepared for transferring to adult care. Only 38% of patients felt that their school or college often had the necessary information to support them with their diabetes.Conclusions This analysis describes the experience of CYP and their parents/carers of T2DM care and highlights areas for improvement. These findings may help to inform recommendations about the development of better patient-centred care for young people with T2DM.